Decreased, Deformed, Defective—How HIV-1 Vpu Targets Peroxisomes - Kristina Hopfensperger (American Society for Microbiology, 2020)
ABSTRACT Peroxisomes are found in essentially all eukaryotic cells and have been described as important hubs in innate sensing and the induction of type III interferons upon viral infection. Nevertheless, it remains poorly investigated how viral pathogens modulate biogenesis or function of peroxisomes to evade innate sensing and restriction. In a recent study, Hobman and colleagues found that the accessory viral protein u (Vpu) of HIV-1 inhibits peroxisome activity by depleting cellular peroxisome pools. This depletion could be ascribed to a Vpu-dependent induction of four microRNAs (miRNAs) that suppress the expression of peroxisomal biogenesis factors PEX2, PEX7, PEX11B, and PEX13. Although the downstream effects on antiretroviral gene expression and HIV-1 replication remain to be determined, these findings provide important insights into peroxisome biogenesis and the modulation of cell organelles by HIV-1 Vpu.